Moral Incongruence and Pornography Use: A Critical Review and Integration. Issue 1 (2nd January 2019) - Grubbs, Joshua B.; Perry, Samuel L.
Abstract : Internet pornography use (IPU) remains a controversial topic within sexual behavior research fields. Whereas some people report feeling dysregulated in their use of pornography, mental health and medical communities are divided as to whether IPU can be addictive. The present review sought to examine this issue more closely, with a focus on how variables other than pornography use, such as moral disapproval and moral incongruence (i.e., feeling as if one's behaviors and one's values about those behaviors are misaligned), might specifically contribute to self-perceived problems around pornography use. Through an examination of recent literature, the present work reviews evidence that moral incongruence about IPU is a common phenomenon and that it is associated with outcomes relevant to current debates about pornography addiction. Specifically, moral incongruence regarding IPU appears to be associated with greater distress about IPU, greater psychological distress in general, greater reports of problems related to IPU, and greater reports of perceived addiction to IPU. The implications of this body of evidence for both clinical and research communities are discussed, and future directions for research are considered.